Performance of Holstein calves from three to twelve months of age - J. Velazco; J. L. Morrill; Robert T. Brandt Jr.; R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1991)
Sixty-four Holstein steers were used to study the effect of season and age on performance. Animals beginning the trial in spring were heavier (P.05) among seasons in average daily gain and feed conversion after 6 mo of age. Rate of growth was reduced after 9 mo of age for all seasons.; Dairy Day, 1991, Kansas State University, Manhattan, KS, 1991;
Keywords: Dairy Day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-175-S; Report of progress (Kansas Agricultural Experiment Station); 640; Dairy; Calves; Growth; Seasons; Age